The impact of China’s digital economy industry development and its structural indicators on carbon emission intensity - Wang, Yitong; Yuan, Yongke; Qian, Xiao; Chi, Yuanying (Frontiers in Environmental Science, 2024)
Introduction The development of the digital economy has a profound impact on industrial economics. The paper conducted an analysis of how China's digital economy and its structural indicators impact carbon emission intensity. The structural indicators comprise three dimensions: digital manufacturing industries, digital service industries, and industrial digitalization. Method This study drew on industrial organization theory and established economic models for empirical test. The paper adopted the measurement framework from the U.S. Bureau of Economic Analysis (BEA) to assess digital economy development through the economic value-added of digital industries. The analysis utilized Input-Output Tables (including extended tables) from 30 Chinese provinces. For empirical modeling, fixed-effects models and Spatial Durbin Models (SDM) were systematically employed. Results and discussion The empirical results show that: 1) at the national level, the development of China’s digital economy industries has a suppressive effect on carbon emission intensity; 2) in terms of spatial effects, the development of digital economy has significant carbon spillover effects, but digital industrialization and industrial digitization present different spatial effect results; 3) from the analysis of regional heterogeneity, in the northeast, central and western regions, the direction of influence of digital industrialization and industrial digitalization on carbon emission intensity is consistent; in the eastern region, the development of digital industrial service sector and industrial digitalization has a suppressive effect on carbon emission intensity, while digital industrial manufacturing sector presents a pro-increasing effect; 4) Non-linear relationship analysis shows that the development of the digital industrial manufacturing sector has a “promoting and then inhibiting” effect on carbon emission intensity. Overall, the impact of digital industry development on carbon intensity exhibits a “promoting increase, then suppressing, then promoting increase” trend. In conclusion, the findings suggest that China’s digital economy industry has entered the low-carbon development stage.